2021
DOI: 10.3390/cells10081952
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Concentration of Anti-SARS-CoV-2 IgG Antibodies Post-COVID-19 Recovery or Post-Vaccination

Abstract: At the end of 2020, population-based vaccination programs with new generation mRNA-based vaccines began almost all over the world. The aim of the study was to evaluate the titer of anti-SARS-CoV-2 IgG antibodies against the S1 subunit of the virus’s spike protein as a marker of the humoral response in 477 patients and the concentration of interferon-gamma as an indicator of cellular response in 28 individuals. In our studies, we used serological enzyme-linked immunosorbent assays. IgG was measured in weeks 2 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
64
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 33 publications
24
64
1
5
Order By: Relevance
“…Nevertheless, the reinfection of these patients has rarely been reported, which indicates that immunological memory (including long-lived plasma cells and memory B cells) might play an important role in preventing reinfection ( Cohen et al., 2021 ; Rodda et al., 2021 ). In addition, some studies have shown that 4 or more months after the vaccination completion, the antibody titer had decreased substantially, even below the seropositive threshold ( Fan et al., 2021 ; Pan et al., 2021b ; Tretyn et al., 2021 ; Yue et al., 2021 ). Although Thomas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the reinfection of these patients has rarely been reported, which indicates that immunological memory (including long-lived plasma cells and memory B cells) might play an important role in preventing reinfection ( Cohen et al., 2021 ; Rodda et al., 2021 ). In addition, some studies have shown that 4 or more months after the vaccination completion, the antibody titer had decreased substantially, even below the seropositive threshold ( Fan et al., 2021 ; Pan et al., 2021b ; Tretyn et al., 2021 ; Yue et al., 2021 ). Although Thomas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Coronaviruses encode four major structural proteins (spike, membrane, envelope, and nucleocapsid) [ 8 ]. Antibodies against spike protein's receptor-binding domain (RBD) have been demonstrated as neutralizing in most studies; therefore, most vaccines target the spike protein RBD and induce immunoglobulin G (IgG) against it [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, neutralizing potency was decreased against some new SARS-CoV-2 variants with mutations on the spike protein. Tretyn et al [35] studied the humoral immune response in 477 individuals after one or two doses of mRNA vaccine in healthy and recovering COVID-19 patients. They concluded that the humoral immune response was diversified and visible as early as two to three weeks after the first dose of the mRNA vaccine, while the level of protection significantly increased after the second dose.…”
Section: Discussionmentioning
confidence: 99%